A comparison of intravenous plus intraperitoneal chemotherapy with intravenous chemotherapy alone for the treatment of gastric cancer: a Meta-analysis - Sheng Yang; Zhang-Chi Pan; Tao Jiang; Rui Feng; Qiang Chen; Qian Xu (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: We aimed to evaluate the effectiveness and safety of intravenous (IV) plus intraperitoneal (IP) chemotherapy compared to IV chemotherapy alone for patients with gastric cancer. Methods: Electronic databases were searched up to June 2013. Two authors independently assessed the quality of included studies. The GRADE System was adopted to rate the level of evidence. Of 392 citations, five RCTs involving 1, 072 patients were included. Results: Overall, a significant improvement in in 1- and 3- and 5-year survival rate was observed in the IV plus IP chemotherapy group (3 RCTs, n=360, RR=1.10, 95% CI, 1.04~1.17), (5 RCTs, n=953, RR=1.22, 95% CI, 1.11~1.35) and (3 RCTs, n=347, RR=1.42, 95% CI, 1.12~1.80), respectively. Results supported a significant decrease in the rate of metastases (1 RCT, n=85, RR=0.41 95% CI, 0.19~0.89) and peritoneal recurrence (2 RCTs, n=297, RR=0.41, 95% CI, 0.26~0.62) in the IV plus IP chemotherapy group, however, the incidence of adverse events was increased. Conclusion: For patients with gastric cancer, IV plus IP chemotherapy can improve the overall survival rate and prevent the distant or peritoneal metastases. An increased risk of neutropenia, peripheral edema and neuropathy was observed.